FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN BENSIN SUPER tt: STUDI KASUS DI DKI JAKARTA (PERIODE APRIL 1997 - DESEMBER 1999) - Vigi Anggaputri; SIwi Nugraheni (Bina Ekonomi, 2000)
The main source of air pollution in DKI Jakarta came from gas emission of vehicles. One of the pollutants which came from exhaust motorized vehicle is lead (Pb) which contributes to the biggest lead pollution in the air. Lead (Pb) is known as a harmful pollutant this paper will focus on the factors influence unleaded gasoline sales, well known as the "Super TT" in Jakarta between April 1997 and December 1999. The result shows that the demand of Super TT is significantly influenced by the price of Premium gasoline and Premix gasoline, meanwhile the impact of Super TT price to the volume of Super TT sale is not significant, although the demand of Super TT is elastic. In addition, Super TT and Premium would be considered as a substitution good, meanwhile Super TT and Premix is categorized as a complementary good.